Uma história da Educação Especial no município de Marilândia-ES: histórias e narrativas (1980-1999) - Gabriel, Emilio (2023)
This study aims to understand part of the history of special education in the city of Marilândia-ES between 1980 and 1999, from the narratives and memories of local education professionals who experienced the process. This subject is relevant because it studies the reality of a municipality in the interior, far from the great centers of debate, and because there is not much research on the implementation of this modality in such locations. As a theoretical basis for reflection and interpretation of the data produced, we used authors who dialogue with the historical-cultural matrix of the development of society, Bakhtin and Vygotsky. Thus, we aim to understand how the process of construction of special education, policies and teacher training took place; understand, through the professionals' statements, evidence of the difficulties faced and the potential of their work with students linked to special education; and to analyze the impacts of official actions in the special educational practice in the municipal schools of Marilândia-ES, between 1980 and 1999. To better achieve these objectives, we took as a basis the qualitative analysis of a historical-cultural nature. As a methodological strategy, we worked with the semi-structured narrative interview, collecting reports from 9 profissionals individually. The reports were recorded using a cell phone application and later transcribed, being divided and analyzed by categories, in the light of our base theorists, as well as other authors who approached the theme of special education from the perspective of inclusive education. We were able to conclude that, in the period in question, the historical trend of the segregation path for the integration of the student with disabilities in the common school was repeated and that, in an embryonic way, the municipality was already preparing for the transition to inclusive education.